Galician Noir Literature and Translation - Iolanda (Madrygal. Revista de Estudios Gallegos, 2024)
This paper performs an analysis of the relationship between noir literature and translation in the Galician literary system based on the assumptions of the Sociology of translation and cultural studies (Sapiro 2008, Heilbron & Sapiro 2016). From the exhaustive data of the Catálogo da tradución galega (Galician translation catalogue) Bitraga, an overview of the literature translated into or from Galician is firstly made, considering places and languages of translation, volume of translated work, genres, and audiences of direct and inverse translation of Galician literary works in the period 1975-2020. Secondly, an overview of the translation of noir literature is developed within the same parameters and, additionally, its chronology, authorship, publishers, collections, and awards received, etc. are also taken into account. The aims of this paper is to contribute to the history of Galician literary translation based on verified and reliable data and to demonstrate the singularity of the current noir fic-tion genre in the Galician literary system. The volume of data on the production and the translation of Galician crime fiction works and the authors of the last decade confirm the vitality of the genre.